Collaborative Promotions Optimizing Retail Supply Chains with Upstream Informaton Sharing - Wiehenbrauk, Daniela; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
Promotions are at the same time beloved and feared by both food retailers and branded goods manufacturers in today$1 (Bs retail environment. Beloved because they attract smart customers and generate an immediate effect on a brand$1 (Bs sale. Feared because there is uncertainty about the competitors$1 (Bbehavior and the actual customer demand leading to high forecast errors. For the retailer, this results in a doom loop of over- or understocking with high inventory costs in the supply chain. Collaboration between retailers and the manufacturer disentangles the doom loop. The thesis reveals the appropriate kind and timing of information and develops a so called Competition Index. Inventory in the supply chain is eliminated and the customer is served better at a lower price. Based on a joint inventory and pricing model and an empirical analysis, it shows that the supply chain efficiency gains from collaborative promotions result in a win for customers, retailers and the manufacturer.s
Promotions and Collaboration in Retailing -- Literature Review -- Retailer Competition -- Empirical Analysis -- Conclusion and Managerial Insights.
Keywords: Economics; Mathematical statistics; Economics, Mathematical; Marketing; Operations research; Economics/Management Science; Operation Research/Decision Theory; Marketing; Game Theory/Mathematical Methods; Production/Logistics/Supply Chain Management; Statistical Theory and Methods